Combined Photo‐Therapies: Nanocarrier‐Mediated Photochemotherapy and Photoradiotherapy (Adv. Healthcare Mater. 8/2018). Issue 8 (25th April 2018) - Denkova, Antonia G.; de Kruijff, Robine M.; Serra‐Crespo, Pablo
Abstract : Recent advancements in nanotechnology create opportunities to combine different treatment modalities such as photothermal and photodynamic therapy with chemo‐or radiotherapy in just one nanocarrier. These new multi—functional nanocarriers have a much better tumor killing efficiency than photo‐induced therapies alone and are expected to reduce side effects usually associated with conventional chemo‐ and radiotherapy. This is reviewed in article number 1701211 by Antonia G. Denkova and co‐workers.